Penerimaan Konsumsi Nasi Beras Hitam Untuk Mencegah Penyakit Diabetes di KWT Zahra - Siti Nurhidayah; Efrin Firmansyah (Journal of Empowerment Community, 2021)
Black rice is one of the functional foods that is safe and recommended for the fulfillment of carbohydrate adequacy, especially for sufferers of degenerative diseases. solve social problems related to the high rate of productive unemployment to be able to participate in and join the program to build a healthy village, (3) Encourage creativity and innovation in the community in utilizing the potential of black rice to increase living standards to be more prosperous, (2) Encourage the creation of food-independent villages and create a prosperous household. The service was carried out from September to December 2018 at KWT Zahra, Parakannyasag Village, Indihiang District, Tasikmalaya City. Activities carried out include the transfer of healthy living technology, the prospect of black rice cultivation, training and demonstrations of cooking mixed black and white rice, and conducting black rice preference tests on KWT members. The results showed that people's preferences based on hedonic quality that black rice did not differ much in terms of hedonic quality when compared to white rice and tended to be neutral based on the level of preference.